A Study of Behavioural Finance in Decision Making - Ms. Taruna Sharma; Ms. Sarika Walia (International Journal of Engineering and Management Research, 2022)
The traits of human behaviour examined in this article have always existed, but the economy seems to have forgotten about them. Given that people are the driving forces behind this economic cosmos, why this is so remains a mystery. Perhaps a plausible explanation is that traditional viewpoints are too closed to the issue and lack the willingness to embrace and comprehend how the psychology of the investor affects his decisions and day-to-day financial movements.